Longitudinal sport motivation among young athletes in intensive training settings: The role of basic psychological needs satisfaction and thwarting in the profiles of motivation - Cece, V.; Lienhart, N.; Nicaise, V.; Guillet-Descas, E.; Martinent, G. (Journal of Sport & Exercise Psychology, 2018)
The purpose of this study was to examine the longitudinal profiles of sport motivation using a 3-wave design (beginning, middle, and end of the season) among a sample of 736 adolescent athletes involved in intensive training centers. The authors explored whether several subgroups of athletes representing distinct motivation profiles emerged from the analyses and whether athletes reporting various scores of satisfaction and thwarting of basic psychological needs (BPNS and BPNT) at time 1 (T1) belonged to distinct motivational profiles at T1, T2, and T3. Results of latent profile transition analyses showed 4 different profiles: highly self-determined, self-determined, moderate autonomous and controlled motivation, moderately self-determined (T1 and T2), and high autonomous and controlled motivation (T3) profiles. Moreover, the likelihood of belonging to particular profiles was significantly predicted by athletes` BPNS and BPNT scores assessed at T1. Thus, a motivational profile approach may prove useful in understanding sport motivation as a dynamic system.